Respon Pertumbuhan dan Hasil Lobak Putih (Raphanus sativus L.) terhadap Pemberian Urine Kelinci dan Pupuk KCl pada Tanah PMK - Yolanda, Farisa; Sasli, Iwan; Ramadhan, Tris Haris (Perkebunan dan Lahan Tropika, 2026)
Growth and Yield Response of White Radish (Raphanus sativus L.) to the Application of Rabbit Urine and KCl Fertilizer in PMK Soil. Radish (Raphanus sativus L.) is a root vegetable of the Brassicaceae family, closely related to cabbage. Based on data from the Central Statistics Agency of West Kalimantan (2021), the productivity of radish in West Kalimantan in 2020 decreased compared to the previous year. Increasing radish production can be achieved through agricultural intensification using Podsolik Merah Kuning (PMK) soil (Ultisol). The main problem of PMK soil is its low fertility. One way to improve the chemical properties of PMK soil is to apply organic fertilizer, namely rabbit urine liquid fertilizer, and inorganic fertilizer, namely KCl. This study aimed to determine the best concentration of rabbit urine and the most effective dose of KCl fertilizer for the growth and yield of white radish in PMK soil. The research was conducted in the experimental field of the Faculty of Agriculture, Tanjungpura University, Pontianak City, from September 15 to October 30, 2024. The experiment used a factorial completely randomized design with two factors. The first factor was rabbit urine concentration (U) at three levels: u1 = 20 ml/L, u2 = 40 ml/L, and u3 = 60 ml/L. The second factor was the KCl fertilizer dose (K) at three levels: k1 = 0.8 g/plant, k2 = 1.2 g/plant, and k3 = 1.6 g/plant. The results showed no interaction between rabbit urine concentration and KCl fertilizer on the growth and yield of white radish in PMK soil. Individually, rabbit urine at 20 ml/L and KCl fertilizer at 0.8 g/plant gave the best results on radish tuber length. However, no optimal and effective dose was found to significantly improve the growth and yield of white radish in PMK soil.